Study of molecular pathways mediating the anti-cancer efficacy of koetjapic acid isolated from sandoricum koetiape against human colon cancer xenograft in immunocompromised mice. - Abdul Majid, Amin Malik Shah (Universiti Sains Malaysia, 2014)
Taking the promising chemotherapeutic efficacy of potassium koetjapate, the results of the present study suggests and recommends to proceed further research activities on potassium koetjapate using clinical trails phase I~ II and ill to evaluate the safety, effective dose and therapeutic efficacy in human patients.